Analysis of the Economic and Socio-Demographic Burden of HPV-Associated Diseases and the Cost-Effectiveness of HPV Vaccination in Russia - Alexander A. Baranov; Alexander V. Plakida; Leyla S. Namazova-Baranova; Mikhail A. Semenov; Olga V. Ilyushina; Yevgeniy V. Guretskiy; Marina V. Fedoseenko; Alla V. Rudakova (Union of pediatricians of Russia, 2019)
Background.The human papillomavirus (HPV) is one of the most common sexually transmitted viruses and, according to WHO, the cause of 7.5% of all women deaths from cancer. Every year, more than 500.000 new cases of HPV-associated cancer are registered in the world, approximately 90% of which fall into cervical cancer category. Aim. The aim of the work was to determine the economic and socio-demographic burden of HPV-associated diseases in Russia by analyzing the following indicators: fertility, life expectancy and cost of vaccines, as well as the impact of HPV vaccination. Methods. Mathematical modeling was performed using epidemiological data on prevalence and mortality of HPV-associated diseases in Russia, taking into account current data on the types of HPV-related diseases, the effectiveness of vaccination, statistics by sex and age structure of diseases, and age-specific birth rates. The calculations were based on 50% and 70% vaccination coverage, and the average life expectancy of 12-year-old girls. Treatment cost was calculated based on the fees charged by mandatory health insurance system. The weighted average cost of 1 dose of quadrivalent vaccine in 2018, and average cost of visiting a pediatrician before each vaccination were taken into account. To estimate the cost, a discount rate of 3.5% per year was used. The economic burden of HPV-associated diseases, direct and indirect medical costs were calculated. Results. The economic burden of HPV-associated diseases is estimated at 63.638 billion rubles. 70% vaccination rate would reduce the economic burden by 41.792 billion rubles, prevent 4,841 deaths from malignant neoplasms and reduce losses associated with a fall in the birth rate by 1,100 children per year. The estimated economic effect of vaccination per vaccinated girl will be 13,327 rubles, and the total economic effect over the entire simulation period will be 31.653 billion rubles. Conclusion. Taking into account the results of modeling, vaccination of 12-year-old girls against HPV in Russia is a cost-effective measure in the prevention of HPV-associated diseases.